2013
DOI: 10.1080/10934529.2013.776852
|View full text |Cite
|
Sign up to set email alerts
|

Behavior ofTypha angustifoliaL. in a free water surface constructed wetlands for the treatment of swine wastewater

Abstract: The objective of this study was to evaluate the behavior of Typha angustifolia L. in nitrogen retention in a Free Water Surface Constructed Wetland (FWS) for the swine wastewater treatment over a three-year operating period. Results show that the behavior of Typha angustifolia L. in a FWS for treatment of swine wastewater is affected by nitrogen concentration, seasonal variation and plant establishment in the system. Indeed, the application of Nitrogen Loading Rates (NLR) between 7.1-14.3 kg TN/ha·d removes 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In this case, over 3 years of operation, the plant N:P:K Foliar biomass presents a value of 968.6 § 10.0 g m ¡2 . Similar to the discussion above about phytotoxic effects, these values are lower than those reported for FWS operation for loads in the range of 0.2 to 69.9 kg TN ha ¡1 ¢d ¡1 , with a value of 1,509.6 § 120.2 g m ¡2 , [8] and for loads in the range of 3.0 to 40.0 kg TN ha ¡1 ¢d ¡1 , with a value of 1,100 to 2,800 g m ¡2 . [4] Evolution of the FWS sediments Figure 6 shows the accumulation of nutrients in sediments in relation to the C/N ratio during the study period.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…In this case, over 3 years of operation, the plant N:P:K Foliar biomass presents a value of 968.6 § 10.0 g m ¡2 . Similar to the discussion above about phytotoxic effects, these values are lower than those reported for FWS operation for loads in the range of 0.2 to 69.9 kg TN ha ¡1 ¢d ¡1 , with a value of 1,509.6 § 120.2 g m ¡2 , [8] and for loads in the range of 3.0 to 40.0 kg TN ha ¡1 ¢d ¡1 , with a value of 1,100 to 2,800 g m ¡2 . [4] Evolution of the FWS sediments Figure 6 shows the accumulation of nutrients in sediments in relation to the C/N ratio during the study period.…”
Section: Resultssupporting
confidence: 66%
“…[8] Plaza de los Reyes et al [8] reported the existence of a relation between the N: P: K ratio and the operational time of the sytem (establishment of macrophyte species). In this case, over 3 years of operation, the plant N:P:K Foliar biomass presents a value of 968.6 § 10.0 g m ¡2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[18,19] Meanwhile, to end 2011 and mid 2012, it had hydraulic loading rates between 1.7 and 9.1 mm d ¡1 from rainfall. [20] The wetland system in the last period (spring 2011 to fall 2012) had nutrient loads about 3,381 kg N ha ¡1 and 1,061 kg P ha ¡1 from taken up of swine slurries by the aboveground vegetal tissue none pruned, soil and remained loads from early 2011.…”
Section: Study Areamentioning
confidence: 99%